Metabolic dysfunction in human skin: Restoration of mitochondrial integrity and metabolic output by nicotinamide (niacinamide) in primary dermal fibroblasts from older aged donors. Issue 10 (29th September 2020) - Oblong, John E.; Bowman, Amy; Rovito, Holly A.; Jarrold, Bradley B.; Sherrill, Joseph D.; Black, Markaisa R.; Nelson, Glyn; Kimball, Alexa B.; Birch‐Machin, Mark A.
Abstract: Alterations in metabolism in skin are accelerated by environmental stressors such as solar radiation, leading to premature aging. The impact of aging on mitochondria is of interest given their critical role for metabolic output and the finding that environmental stressors cause lowered energy output, particularly in fibroblasts where damage accumulates. To better understand these metabolic changes with aging, we performed an in‐depth profiling of the expression patterns of dermal genes in face, forearm, and buttock biopsies from females of 20–70 years of age that encode for all subunits comprising complexes I‐V of the mitochondrial electron transport chain. This complements previous preliminary analyses of these changes. "Oxidative phosphorylation" was the top canonical pathway associated with aging in the face, and genes encoding for numerous subunits had decreased expression patterns with age. Investigations on fibroblasts from older aged donors also showed decreased gene expression of numerous subunits from complexes I‐V, oxidative phosphorylation rates, spare respiratory capacity, and mitochondrial number and membrane potential compared to younger cells. Treatment of older fibroblasts with nicotinamide (Nam) restored these measures to younger cell levels. Nam increased complexes I, IV, and V activity and gene expression of representative subunits. Elevated mt‐Keima staining suggests a possible mechanism of action for these restorative effects via mitophagy. Nam also improved mitochondrial number and membrane potential in younger fibroblasts. These findings show there are significant changes in mitochondrial functionality with aging and that Nam treatment can restore bioenergetic efficiency and capacity in older fibroblasts with an amplifying effect in younger cells. Abstract : A decline in mitochondrial quality was observed in primary human skin fibroblasts with age, with a decrease in mitochondrial complex gene expression, oxidative phosphorylation rates, spare respiratory capacity, mitochondrial number, membrane potential, and mitophagy. The addition of Nam (nicotinamide, vitamin B3) improved these age‐related changes in cells from older aged individuals to levels observed in younger individuals, with an amplifying effect seen in younger cells.